Incidencia de las actividades hidrocarburíferas en el desarrollo de microempresas comunitarias del bloque 18 en la amazonía ecuatoriana - Cárdenas Velasco, Mauro (2014)
This paper analyzes and researches the growth and sustainable development of community micro-enterprises in the zone of influence of mining activities and hydrocarbon operations in Block 18. It is framed in implementing policies and programs of Corporate Social Responsibility aimed at strengthening community development.During the research, it was identified that the contribution of such community microenterprises exercise a positive impact on the generation of jobs for the population, which in turn has improved the quality of life of its inhabitants, recognizing that sustainable economic growth and community relationships are essential to meet individual and collective needs of the population.